The lifework of Architect Antonio A. Flores - Lanyi, Br. Bela (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2023)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/9530/8410